2023
DOI: 10.1002/jmv.28589
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‐193a/b‐3p during HPV‐induced cervical carcinogenesis contributes to anchorage‐independent growth through PI3K–AKT pathway regulators

Abstract: Cervical cancer is caused by a persistent infection with high‐risk types of human papillomavirus (HPV) and an accumulation of (epi)genetic alterations in the host cell. Acquisition of anchorage‐independent growth represents a critical hallmark during HPV‐induced carcinogenesis, thereby yielding the most valuable biomarkers for early diagnosis and therapeutic targets. In a previous study, we found that miR‐193a‐3p and miR‐193b‐3p were involved in anchorage‐independent growth. This study aimed to delineate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The 3'UTR regions were amplified from 50 ng of genomic DNA from FK18B cells using Phusion™ High‐Fidelity DNA Polymerase (Thermo Fisher Scientific) according to the manufacturers protocol. Subsequently, the amplified regions were cloned into pmirGLO Dual‐Luciferase miRNA Target Expression Vector plasmid (Promega), as described previously 21 . Primers used for cloning of luciferase reporter assays are listed in Supplementary File .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3'UTR regions were amplified from 50 ng of genomic DNA from FK18B cells using Phusion™ High‐Fidelity DNA Polymerase (Thermo Fisher Scientific) according to the manufacturers protocol. Subsequently, the amplified regions were cloned into pmirGLO Dual‐Luciferase miRNA Target Expression Vector plasmid (Promega), as described previously 21 . Primers used for cloning of luciferase reporter assays are listed in Supplementary File .…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the amplified regions were cloned into pmirGLO Dual-Luciferase miRNA Target Expression Vector plasmid (Promega), as described previously. 21 Primers used for cloning of luciferase reporter assays are listed in Supplementary File 2. Mutagenesis of target sites was performed using the Q5 Site-Directed Mutagenesis Kit (New England Biolabs, Ipswich, MA, USA) according to the manufacturer's instructions.…”
Section: Luciferase Assaymentioning
confidence: 99%
“…MicroRNAs, a class of single-stranded and highly-conserved small non-coding RNAs, suppress gene expression at post-transcriptional or translational levels, and is deeply implicated in cardiac development and disorders. Previous studies on the functions of miR-193b-3p were mainly focused on tumor [47,48], in ammation [49,50], and metabolism [36,51]. Recent advances have revealed that miR-193b-3p participates in the regulation of pulmonary hypertension in heart failure[36], cardiac hypertrophy [37] and the apoptotic pathway in myocardial ischemia/reperfusion injury [38].…”
Section: Synaptotagmin-1 Is Suppressed By Mir-193b-3pmentioning
confidence: 99%